Jurnal Pelaksanaan Seminar Program Kerja Mengajar di Sekolah SD di Kecamatan Kulo Khususnya di Desa Kulo - Muhammad Afdhal Muis; Amrul Mu’minin; Nur Sri Handayani; Muhammad Mastricht Abdul Razil; Istita Mutmainna; Yuliana Fajrin; Masda Nugraha; Muhammad Takbir; Santri Sahar (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This journal discusses the implementation of This seminar discusses the importance of Cultivating Elementary School Children's Creativity through Project-Based Learning": This seminar discusses how to integrate creative projects into the elementary school curriculum to enhance children's creativity and skills.